Unusual Presentation of a Sphenoidal Sinus Neuroendocrine Tumor: A Case Report and Review of Literature - Kaur, Jasmeet (Cureus, 2021)
Neuroendocrine tumors (NETs) have a heterogeneous pathology and indolent behavior, with the most common location being the gastrointestinal tract and then the lungs. The head and neck are rare sites of NET presentation with varied clinical signs and symptoms, which occasionally delay the diagnosis, thereby leading to an advanced stage at presentation. We present a rare case of paranasal sinus small cell neuroendocrine tumor and perform a review of the literature. A 71-year-old man presented with continuous bleeding from the left nostril and nasal congestion without any prior medical history. Clinical examination revealed nasal congestion, rhinorrhea, postnasal drip, and active bleeding. The laboratory data were within normal limits. Imaging studies showed a left sphenoid sinus mass extending to the left ethmoid sinus with a break in the cribriform plate encephalocele. An enlarged lymph node measuring 2.2 cm was noted in the left neck and supraclavicular region. The evaluation through stereotactic endoscopic sinus surgery and biopsy revealed left nasopharyngeal, sphenoid sinus, and ethmoid sinus masses. Pathologic biopsy findings were consistent with high-grade, malignant, small, round blue cell tumors. Immunohistochemical analysis confirmed high-grade small cell neuroendocrine carcinoma. The patient was diagnosed with stage IV (TXN2bM0, T: tumor size, N: lymph node, M: metastasis) high-grade neuroendocrine tumor of the left paranasal sinus. He was treated with concurrent chemoradiation therapy with two cycles of etoposide and cisplatin and radiation therapy with proton beam radiation therapy followed by two cycles of adjuvant etoposide cisplatin chemotherapy. The patient showed a good response to the treatment, as confirmed using imaging. He is currently being regularly followed up with serial imaging.